Pengaruh Peltihan Terhadap Kinerja Pengisian Data Inovsi Daerah Kabupaten Boyolali Tahun 2024 - Raflentio Dims Rizki; Aditya Liliyan (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the effect of training on the performance of regional innovation data entry in Boyolali Regency in 2024 through the BI-SMART system. The population of this research consisted of 83 civil servants (ASN) serving as BI-SMART application operators, with a sample of 30 ASNs selected using purposive sampling. A quantitative approach was employed using a Likert-scale questionnaire, which was tested for validity and reliability. Data analysis was performed using simple linear regression preceded by classical assumption tests (normality and heteroskedasticity tests). The results show that training has a positive and significant effect on the performance of innovation data entry, as evidenced by a t-value of 4.721 and a significance level of 0.000 (<0.05). These findings confirm that structured and practical training can improve the accuracy, completeness, and timeliness of data entry. The study contributes theoretically by strengthening the concepts of transfer of training, adult learning, and Kirkpatrick’s evaluation model, while practically providing strategic recommendations for the Boyolali Regency Government in designing more effective training programs to support data-driven regional innovation governance.